Stock Assessment Using LBB Method for Eight Fish Species From the Bohai and Yellow Seas - Wang, Yibang; Wang, Yuanchao; Liu, Shude; Liang, Cui; Zhang, Hui; Xian, Weiwei (Frontiers in Marine Science, 2020)
Eight common and commercially important marine fishes from coastal and offshore areas of Shandong Province, China, were assessed using the ‘Length-based Bayesian Biomass’ estimator (LBB） method. These species were Scomber japonicus (chub mackerel), Sebastiscus marmoratus (false kelpfish), Hexagrammos otakii (fat grrenling), Thryssa kammalensis (kammal thryssa), Gadus macrocephalus (Pacific cod), Setipinna taty (scaly hairfin anchovy), Sillago sihama (silver sillago) and Lophius litulon (yellow goosefish). LBB is a new powerful, yet simple approach to evaluate a fisheries’ status using length and frequency data. Shandong Province’s coastal areas, adjacent to the Yellow and Bohai Seas, are an important fishing ground of China, where the 2018 catch of three of these species, yellow goosefish, chub mackerel, and Pacific cod, yielded up to 57,200, 21,100, and 1330 tons, respectively. The ratios of current relative to unexploited biomass (B/B0) is smaller than the relative biomass that can produce MSY (BMSY/B0) in all 8 stocks, indicating overfishing. Also, the sizes at first capture were well below optimal, suggesting that larger mesh sizes would be beneficial. Our study provides evidence that LBB is an efficient and accurate method to evaluate the fishery resources in the Yellow and Bohai Seas, especially when length-frequencies are the only available data. Also, LBB provided evidence useful for the management of the costal fishery resources of Shandong Province.